2020
DOI: 10.1039/d0sm00395f
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear theory of wetting on deformable substrates

Abstract: The spreading of a liquid over a solid material is a key process in a wide range of applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 99 publications
0
38
0
Order By: Relevance
“…This relationship between surface properties and bulk rheology for different crosslinking densities is not captured by the nonlinear elastic model of Neo-Hookean solids [29,30]. Here we interpret the results by considering the surface elasticity of the gels [18].…”
Section: Resultsmentioning
confidence: 81%
“…This relationship between surface properties and bulk rheology for different crosslinking densities is not captured by the nonlinear elastic model of Neo-Hookean solids [29,30]. Here we interpret the results by considering the surface elasticity of the gels [18].…”
Section: Resultsmentioning
confidence: 81%
“…The method can also be used to deal with more complicated problems, e.g. dynamic wetting on soft substrates or other geometries ( [11,34]). These problems will be left for future work.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, experiments have demonstrated that the dynamics of drop impacts can be controlled by the softness of the solid (Pepper, Courbin & Stone 2008;Chen & Li 2010;Chen et al 2016;Howland et al 2016;Langley, Castrejón-Pita & Thoroddsen 2020). The deformations of the substrate can affect the dynamics after contact, either by absorbing some of its energy or through the contact line motion (Andreotti & Snoeijer 2020;Dervaux, Roché & Limat 2020). The high lubrication pressure can also deform the substrate before contact occurs, as recently observed in experiments (Langley et al 2020) as well as in numerical and theoretical work (Pegg, Purvis & Korobkin 2018;Henman, Smith & Tiwari 2021).…”
Section: Introductionmentioning
confidence: 99%